Prevalence of unnecessary laboratory tests and related avoidable costs in intensive care unit - Anderson Magalhães Oliveira; Marcio Vasconcelos Oliveira; Claudio Lima Souza (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction:Because of the increase in diagnostic resources, laboratory tests have become an essential tool in diagnostic elucidation. Therefore, we observe an increase in the number of tests request.Objectives:To determine the prevalence of laboratory tests requests by the intensive care unit (ICU) of the General Hospital at southwest Bahia, and to anticipate the expenses with unnecessary laboratory tests, indicating avoidable costs, and aiming at rationalization of laboratory tests use.Methods:This is a cross-sectional retrospective study, in which a survey on medical records and laboratory tests results of patients admitted to the ICU was conducted, in the period from August to September 2013.Results:The sample consisted of 105 patients, 58.1% males, 47.6% aged between 18-59 years. During the period, 12.217 laboratory tests were ordered, of which 49.4% was within the normal limits. The more requested exams were: complete blood count, sodium, and potassium. A number of 1.750 laboratory tests could be evaluated according to criteria established in the literature, among them, 719 (41%) were considered unnecessary. A greater number of requests (29%) were observed on Mondays, compared with the average of the rest of the week.Conclusion:Significant number of unnecessary testing was found, with occurrence pattern on Monday and not dependent on age or length of stay. The data indicate the need to implement guidelines or protocols for ordering laboratory tests in the ICU, which have proven effective in helping the prescribing professional in their clinical practice, and contribute to optimize for health care spending.